Executive Committee Minutes 2015-11-05 - Academic Senate:::::::::
Chair Report. Provost Report. Vice Chair Report. Agenda approved. Minutes of 10/22 approved. Revised Senate Diversity Subcommittee charge approved for Senate agenda. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. Potential new charge for APC discussion. EPC Report. CFA Report. Associated Students Report. Input on working draft for Faculty Retreat. WASC worksheet process. Senate Agenda